The longest autumn - Avery, Amy (Flatiron Books, 2024)
"For fans of Ariadne, a spellbinding debut fantasy about a human who gets trapped with the god of Autumn, who brings with him life-threatening danger and a forbidden romance. Under the right circumstances, would even a god fall? Tirne is one of four humans rigorously selected to usher the turn of the seasons into the mortal world. Every year, she escorts the taciturn god Autumn between the godly and human realms. Autumn's seasonal stay among mortals brings cooler weather, changing leaves, and the harvest of apples and gourds until Winter takes his place. This year, the enchanted Mirror that separates their worlds shatters after Tirne and Autumn pass through, trapping both of them in the human realm. As the endless autumn stretches on, crops begin to fail and the threat of starvation looms. Away from the magic of the gods' home, Tirne's debilitating headaches return with a vengeance. Worse, Autumn's extended stay in the human realm turns him ever more mortal and vulnerable, stirring a new, forbidden attraction to Tirne. While the priesthood scrambles to find a way to reassemble the Mirror, Tirne digs into the temple's secrets and finds an unlikely ally-or enemy-in the enigmatic sorcerer and master of poisons, Sidriel. Thrown into a world of mystery, betrayal, and espionage as she searches for the truth, might Tirne lose her morals, her hard-earned position, and the illicit spark between her and Autumn?"--